Associação da proteína sericina ao exercício de natação na regeneração do músculo plantar, após lesão compressiva do nervo isquiático de ratos Wistar - Santana, André Júnior (2017)
Peripheral nerve damage causes a number of morphological changes, resulting in functional, nerve and muscle complications. There are several therapeutic measures applied in rehabilitation, such as physical exercise in the aquatic environment, which has been extensively studied in terms of functional improvement, although its regenerative potential needs more evidence. Also, it is important to search for substances with therapeutic potential and that can be used in association with physical exercise, in order to intensify recovery. The protein biopolymer, sericin, obtained from the cocoon of the silkworm (Bombyx mori), presents a series of important regenerative pharmacological effects, with cicatrizant action in the treatment of burns, improvement in the aerobic performance and the oxidation of fat at rest. In this sense, the objective of this study was to analyze the effect of sericin associated or not to physical swimming exercise on the muscular recovery of Wistar rats, submitted to sciatic nerve injury. The experiment was carried out in a sample composed of 40 animals, 10 ± 2 weeks old, randomly divided into five groups: Ct: control; Ls: injury; Being: injury + sericin; Nat: injury + swimming; Ser + Nat: injury + sericina + physical exercise. The animals were anesthetized and submitted to compression injury of the right sciatic nerve. Immediately after the nerve compression, a dose of 100 μL of hydrolyzed sericin was applied to the injured nerve in Ser and Ser + Nat animals. On the other hand, the animals of the Nat and Ser + Nat groups, 72 hours after the injury, were treated with resisted physical exercise of swimming, with overload of 10% of body weight, during three weeks, five days a week. The animals performed fifteen minutes of swimming in the first week, 20 minutes in the second and 25 minutes in the third week. During the treatment, the grip strength of the right pelvic limb of all animals was evaluated. At the end of the experimental period, the animals were anesthetized for dissection and collection of the plantar muscle, and the proximal part was processed and analyzed histomorphologically, and the distal for histoenzymological analysis. Regarding the functional data of muscular strength of grip, morphology and morphometry of the 8 neuromuscular junctions, no significant influence on the neuromuscular regeneration process was observed. The same occurred with the musculoskeletal properties, which did not suffer significant changes in the association of sericin and swimming. Although physical swimming exercise alone was efficient in maintaining the intramuscular conjunctiva, the association with sericin was not able to alter the plantar muscle phenotype, although experimental axonotmosis did so